Efek sertifikasi RSPO dan determinan lainnya terhadap kinerja keuangan perusahaan perkebunan kelapa sawit di Indonesia - Leo Rio Ependi Malau; Khoiru Rizqy Rambe (Jurnal Ekonomi Modernisasi, 2022)
The palm oil industry is in the spotlight because it is always associated with issues of deforestation, loss of biodiversity, increased emissions, and land conversion. RSPO (Roundtable on Sustainable Palm Oil) exists as one of the certification labels to ensure sustainable palm oil plantation practices. However, RSPO certification has an impact on increasing costs so it affects the company's financial performance. In addition, the company's financial performance is influenced by many internal and external factors. This study aims to analyze the effect of RSPO certification and other factors on the financial performance of palm oil companies in Indonesia as proxied by Return on Assets (ROA), analysis using Static Panel Regression. This study used secondary data in the form of annual reports for the 2015-2021 period from 15 palm oil companies listed on the Indonesia Stock Exchange (IDX). Static Panel Regression results with Fixed Effect Model (FEM) show that RSPO certification has a positive and significant effect on ROA. The results show the companies that have RSPO certification have a greater ROA than companies that do not have certification with a difference of 2.04%. Other factors that have a positive effect on ROA are company size and international CPO prices. While the Debt Asset Ratio (DAR) and Cost of Goods Sold (COGS) have a negative effect on ROA.